Formulasi dan Uji Mutu Fisik Sediaan Krim Ekstrak Etanol 96% Rimpang Kunyit sebagai Kandidat Penyembuh Luka - Maria Ulfa, Ana (Indonesian Journal of Pharmaceutical Education, 2024)
The use of traditional medicine has become widespread and deeply rooted in various cultures. One of the medicinal plants commonly used for wound healing is turmeric (Curcuma longa). This study aims to formulate and develop a topical cream from the 96% ethanol extract of turmeric rhizome as a wound healer by conducting phytochemical screening and evaluating the stability of the cream preparation. Phytochemical analysis confirmed the presence of active compounds such as alkaloids, flavonoids, saponins, and tannins, which contribute to anti-inflammatory and wound-healing properties. The homogeneity test showed that the cream was uniform, with a distinctive turmeric aroma. The pH value was 5, which aligns with the safe range for skin applications (4.5–6.5). However, the spreadability test result was 3 cm, which is below the standard range of 5–7 cm, indicating that further optimization is needed. In conclusion, the formulated turmeric cream meets several quality standards but requires improvements in formulation, particularly in enhancing its spreadability by optimizing additional ingredients to achieve better performance.